A study of the consumer market of fresh fruit and vegetables in the Western Cape : a psychographic study - Kohlberg, Christine Margaret (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Comm.) -- University of Stellenbosch, 1986.